Imag(in)ing the war in Japan : representing and responding to trauma in postwar literature and film - Stahl, David C., 1959-; Williams, Mark, 1957- (Brill's Japanese studies library ;, 2010)
This study of a series of artistic representations of the Asia Pacific War experience in a variety of Japanese media is premised on Walter Davis' assertion that traumatic events and experiences must be 'constituted' before they can be assimilated, integrated and understood. Arguing that the contribution of the arts to the constitution, integration and comprehension of traumatic historical events has yet to be sufficiently acknowledged or articulated, the contributors to this volume examine how various Japanese authors and other artists have drawn upon their imaginative powers to create affect-